2016
DOI: 10.1093/jee/tow008
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Entomopathogenic Fungi as Biological Control Agents of Diamondback Moth (Lepidoptera: Plutellidae) and Compatibility With Chemical Insecticides

Abstract: The objectives were to evaluate the efficiency of entomopathogenic fungi against Plutella xylostella (L.) and the compatibility of the most virulent isolates with some of the insecticides registered for use on cabbage crops. Pathogenicity tests used isolates of Beauveria bassiana, Metarhizium rileyi, Isaria fumosorosea, Isaria sinclairii, and Lecanicillium muscarium standardized at a concentration of 10(7) conidia/ml. Cabbage leaf discs were immersed in these suspensions, and after evaporation of the excess wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 50 publications
0
34
0
4
Order By: Relevance
“…In our previous studies, it was found from many different fungal candidates that M. flavoviride WSWL51721 has good potential in controlling WFT adults, in which the mortality reached 82.65% at a concentration of 1.0 × 10 7 conidia/mL [26]. The compatibility levels between different chemical insecticides and EPF have been shown to be different [19]. We chose three chemical insecticides-imidacloprid, buprofezin, and abamectin-that have been commonly used to control WFT in the field.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous studies, it was found from many different fungal candidates that M. flavoviride WSWL51721 has good potential in controlling WFT adults, in which the mortality reached 82.65% at a concentration of 1.0 × 10 7 conidia/mL [26]. The compatibility levels between different chemical insecticides and EPF have been shown to be different [19]. We chose three chemical insecticides-imidacloprid, buprofezin, and abamectin-that have been commonly used to control WFT in the field.…”
Section: Discussionmentioning
confidence: 99%
“…The fungal strain culture was performed as described in Section 2.2. After autoclaving, when the SDA medium temperature dropped to 45°C, but was not yet solidified and would not affect the pesticide activity [19], each different concentration of pesticide prepared with sterile distilled water was added to the culture medium for homogenization, and then poured into the Petri dishes for solidification. Next, 4 mm diameter fungal strain cores were taken from the M. flavoviride cultures and placed upside down in the middle of Petri dishes containing SDA medium with 0 (control), 10, 50, and 100 ppm of imidacloprid, buprofezin, and avermectin solution, respectively.…”
Section: Radial Hyphal Growth Test In the Presence Of Insecticidesmentioning
confidence: 99%
See 1 more Smart Citation
“…The broken line inset box indicates the common microbial determinants of both insecticidal and nematicide capacity. Duarte et al, 2016;Gonzalez et al, 2016;Khan et al, 2016;Malekan et al, 2015;Mascarin and Jaronski, 2016;QuesadaMoraga et al, 2006;Ramanujam et al, 2014;Safavi, 2013;Xu et al, 2009 Metarhizium anisopliae Haase et al, 2015;Monteiro et al, 2012;Ramanujam et al, 2014;Yang et al, 2012HezeSNPV Helicoverpa zea Gemstar, HzNPV CCAB Haase et al, 2015Lacey et al, 2015;Rowley et al, 2011 MabrNPV Mamestra brassicae;H. armigera;S.…”
Section: Figmentioning
confidence: 99%
“…However, the selection pressure induced by excessive applications may lead to the development of resistance in these populations. To minimize this problem, different biological control agents can be used, especially specific entomopatogenic microorganisms (DUARTE et al, 2016).…”
mentioning
confidence: 99%